Diagnosis and Therapy of Iron Deficiency Anemia During Pregnancy: Recommendation of the Austrian Society for Gynecology and Obstetrics (OEGGG) - Fischer, Thorsten; Helmer, Hanns; Klaritsch, Philipp; Fazelnia, Claudius; Bogner, Gerhard; Hillerer, Katharina M.; Wohlmuth, Christoph; Jaksch-Bogensperger, Heidi; for the Board of the Austrian Society for Gynecolgy and Obstetrics (OEGGG) (Geburtshilfe und Frauenheilkunde, 2022)
This overview analyzes the data on the controversial therapy of iron substitution during pregnancy, the diagnosis of iron deficiency anemia and the indication-related therapy, and is the first recommendation issued by the OEGGG on the appropriate therapy. The effects of anemia during pregnancy on postnatal outcomes have been intensively investigated with heterogeneous results. A final scientific conclusion with regards to the “optimal” maternal hemoglobin level is limited by the heterogeneous results of various studies, many of which were conducted in emerging nations (with different dietary habits and structural differences in the respective healthcare systems). The current literature even suggests that there may be a connection between both decreased and increased maternal serum hemoglobin concentrations and unfavorable short-term and long-term neonatal outcomes. In Austria, 67 percent of pregnant women take pharmacological supplements or use a variety of dietary supplements. Clinically, the prevalence of maternal anemia is often overestimated, leading to overtreatment of pregnant women (iron substitution without a medical indication). To obtain a differential diagnosis, a workup of the indications for treatment should be carried out prior to initiating any form of iron substitution during pregnancy. If treatment is medically indicated, oral iron substitution is usually sufficient. Because of the restricted approval and potential side effects, medical indications for intravenous iron substitution should be limited. Intravenous iron substitution without a prior detailed diagnostic workup is an off-label use and should only be used in very limited cases, and women should be advised accordingly.Die vorliegende Übersicht und erstmalige Empfehlung soll die Datenlage zur kontrovers diskutierten Therapie der Eisensubstitution während der Schwangerschaft, deren Diagnose und indikationsbezogenen Therapie bewerten. Die Auswirkungen einer Anämie während einer Schwangerschaft auf das postnatale Outcome sind Gegenstand intensiver Forschung mit noch immer widersprüchlichen Erkenntnissen. Eine abschließende wissenschaftliche Bewertung eines „optimalen“ maternalen Hämoglobin-Wertes ist durch die unterschiedlichen Studienergebnisse, die überwiegend aus sogenannten Schwellenländern mit spezifischen Ernährungsgewohnheiten und strukturellen Unterschieden in den jeweiligen Gesundheitssystemen stammen, nur eingeschränkt möglich. Der Trend der Datenlage lässt einen Zusammenhang sowohl von erniedrigten als auch erhöhten maternalen Serum-Hämoglobin-Konzentrationen mit einem ungünstigen kurz- und langfristigen neonatalen Outcome als wahrscheinlich erscheinen. In Österreich supplementieren 67% der Schwangeren pharmakologisch oder nutritiv Eisenprodukte. Die Prävalenz der maternalen Anämie wird dabei klinisch häufig überschätzt und führt konsekutiv zu einer Überbehandlung von Schwangeren (Eisensubstitution ohne Indikation). Vor jeder Eisensubstitution während einer Schwangerschaft sollte daher die Indikationsstellung auch in Hinblick auf die Differenzialdiagnosen abgewogen werden, bei richtiger Indikationsstellung reicht eine orale Eisensubstitution meist aus. Aufgrund der Zulassung und des potenziellen Nebenwirkungsprofils sind die Anforderungen an eine intravenöse Eisensubstitution streng zu stellen. Eine intravenöse Eisensubstitution ohne vorausgegangene vollständige Anämiediagnostik ist als eine Therapie im Off-Label-Use restriktiv zu indizieren und auch als solche aufzuklären.
Keywords: pregnancy; anemia; hemoglobin; iron substitution; neonatal outcome